Financial feasibility analysis of salted fish marketing business in Pasar Belakang Sibolga City - Adi Harpansyah; Eddiwan Eddiwan; Husnul Yaqin Harahap; Tirta Anugerah; Tika Nisari (Universitas Teuku Umar, 2026)
The salted fish marketing business in Pasar Belakang Village, Sibolga Kota District, Sibolga City has developed as a solution to the low absorption of fresh fish in the market while also providing employment opportunities for the local community. However, this business faces challenges related to fluctuations in the prices of raw materials, which affect production costs and profitability. The purpose of this study is to analyze the total costs, revenues, and profits, as well as to assess the financial feasibility of salted fish marketing businesses in Pasar Belakang Village, Sibolga Kota District, Sibolga City. This research employed a survey method involving 27 business actors. The data were analyzed using profitability analysis, Break Even Point (BEP), Revenue Cost Ratio (R/C), Return on Investment (ROI), and Payback Period (PP). The findings indicate that business actors who purchase ready-made salted fish incurred an average investment cost of Rp34,230,130, fixed costs of Rp871,010, and variable costs of Rp110,767,435 per month, with an average sales volume of 4,205 kg, revenues amounting to Rp121,330,435, and profits of Rp9,691,990. Meanwhile, businesses producing salted fish independently required an investment cost of Rp54,418,750, fixed costs of Rp1,591,025, and variable costs of Rp94,091,250 per month, with an average sales volume of 6,975 kg, revenues of Rp116,500,000, and profits of Rp20,817,725. The feasibility analysis shows that both types of businesses are financially viable, with BEP values of 347 kg and 495 kg, R/C ratios of 1.09 and 1.22, ROI of 28% and 38%, and Payback Periods of 0.29 years (3.48 months) and 0.22 years (2.64 months), respectively. Based on these results, the salted fish marketing business in Pasar Belakang Village, Sibolga Kota District, Sibolga City is declared financially feasible, with independently producing businesses demonstrating better financial performance.